2013
DOI: 10.1155/2013/267278
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Serum Skin Test versus Autologous Plasma Skin Test in Patients with Chronic Spontaneous Urticaria

Abstract: Previous studies indicate that 25–45% of chronic urticaria patients have an autoimmune etiology. Autologous serum skin test (ASST) and autologous plasma skin test (APST) are simple tests for diagnosing chronic autoimmune urticaria (CAU). However, there are still some questions about the specificity of these tests. This study consisted of 50 patients with chronic spontaneous urticaria (CSU) and 50 sex- and age-matched healthy individuals aged 18 years, and older. A total of 31 (62%) patients and 5 (10%) control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…Moreover, hypothyroidism or subclinical hypothyroidism was more frequent than hyperthyroidism in a large sample of 12,778 patients with CSU . In most studies (three of five), but not all studies, patients with CSU were found to have significantly higher rates of hypothyroidism and hyperthyroidism than HCs and patients without CSU.…”
Section: Resultsmentioning
confidence: 84%
“…Moreover, hypothyroidism or subclinical hypothyroidism was more frequent than hyperthyroidism in a large sample of 12,778 patients with CSU . In most studies (three of five), but not all studies, patients with CSU were found to have significantly higher rates of hypothyroidism and hyperthyroidism than HCs and patients without CSU.…”
Section: Resultsmentioning
confidence: 84%
“…Furthermore, an exact relationship in CSU patients between having higher autoimmune disease with determined autoantibody and ASST positivity was written in guidelines [1], even though there were opposite results advocating usefulness of ASST in showing autoimmunity [27,28]. Finally, it was emphasized to look at thyroid autoantibodies although there was no significant difference of ASST between the CSU group and the control group [29]. Likewise, this study showed that clinically thyroiditis and/or abnormality in thyroid tests was significantly higher in the CSU group than the AU and healthy groups.…”
Section: Thyroid Function Test and Total Ige Resultsmentioning
confidence: 99%
“…23 But, less when compared to the study done by Verma et al in which among 35 patients with history of urticaria 60% had positive ASST. 17 Kulthanan et al reported out 7 patients with family history of urticaria 2 (9.5%) were positive to ASST. 10 Similar to previous studies, we also observed in our study that there was no statistically significant correlation between family history and ASST positivity (p=0.83).…”
Section: History Of Atopymentioning
confidence: 98%
“…The present study is comparable to the studies done by Verma et al, Vohra et al, Ganguly et al in which patients with angioedema had ASST positivity of about 54.5%, 59%, and 60% respectively; but, comparatively lesser to the study done by Sabroe et al which showed 86.9% ASST positivity in patients with angioedema. 4,14,17,18 However few studies done by Kulthanan et al and George et al reported a lower percentage of ASST positivity among patients with angioedema which was only 7.05% and 15% respectively. 10,19 There is no statistically significant association between ASST positivity and angioedema (p=0.13) which is similar to previous studies.…”
Section: Angioedemamentioning
confidence: 99%